Safety and efficacy of chocolate balloon in the treatment of infrapopliteal artery disease - Ridong Wu; Qingqi Yang; Mian Wang; Zilun Li; Chen Yao; Guangqi Chang (CVIR Endovascular)
Abstract Objective To evaluate the safety and efficacy of chocolate balloons in patients with chronic limb-threatening ischemia (CLTI) and infrapopliteal artery disease, and compare them with conventional balloons. Methods This single-center retrospective study included 167 patients with CLTI and infrapopliteal who underwent endovascular intervention with or without chocolate balloons from September 1, 2019 to June 30, 2023. The primary endpoint was amputation-free survival (AFS). Secondary endpoints included major amputation, the absence of clinically driven target lesion revascularization (CD-TLR), the incidence of flow-limiting dissection, below-the-knee (BTK) stent implantation, change in Rutherford clinical grade, procedural success, and major adverse cardiovascular events (MACEs). Patients were followed at 30 days, 6 months, and 12 months to assess symptom improvement, vascular patency as determined by dual-function ultrasound or angiography, and survival. Results At 12 months, AFS was noted in 78.1% of patients in chocolate balloon group and 70.7% of those in conventional balloon group (p = 0.37). The chocolate balloon group demonstrated a significantly higher rate of CD-TLR absence, with 84.0% compared to 69.4% in the conventional balloon group (p = 0.04). The chocolate balloon group had a major amputation-free rate of 92.8%, slightly better than the 89.5% in the conventional balloon group (p = 0.58). Notably, the chocolate balloon group significantly reduced flow-limiting dissection (p = 0.02) and BTK stent implantation (p = 0.03) compared to the conventional balloon group. Conclusion Chocolate balloon reduces the incidence of flow-limiting dissection and BTK stent implantation in patients with CLTI and infrapopliteal. Compared with conventional balloons, there was less lesion revascularization at 12 months, but no significant benefit was found in improving ASF and reducing major amputation of the affected limb.